Performance and Economic Analysis of Solar Water Pump System Laboratory Scale - Usman, Usman; Sunding, Alang; Parawangsa, Akbar Naro (Jurnal Teknologi Terapan, 2018)
The dependence of solar radiation in generating electricity by PV will have an impact on the PVWPS performance, besides The PVWPS consists many components with different characteristics. Thus this research will investigation the performance conduct economic analysis of PVWPS. To achieve that objective measurement of data starting at 09.00 until 16.00. The data are solar radiation, voltage and current of PV/pump and the time required to fill the container with a certain volume. Analysis data is using the equations that have been predetermined and comparison other research. The results obtained that the water discharge generated by PVWPS will be proportional to solar radiation, as a result the production of electricity generated by PV. The pump efficiency and system is proportional to solar radiation. This phenomenon is the effect of water debit dependence on solar radiation. The result of economic analysis is the price of electricity generated by SPATS is relatively cheap and the water cost for every m3 is inversely proportional to the water discharge generated by the pump.